ANALISIS PREDIKSI HARGA SAHAM PT GUDANG GARAM TBK INDONESIA - Michael, Michael; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2024)
This research aims to predict PT Gudang Garam Tbk's stock prices using the ARIMA method. Historical daily stock price data were analyzed to detect trends and seasonality. The ARIMA model was developed and tested, demonstrating significant predictive accuracy. Evaluation metrics such as Mean Absolute Error and Root Mean Squared Error were employed for performance assessment. The research contributes to stock price prediction methodologies, offering practical implications for investors and financial analysts. In conclusion, the study establishes a robust foundation for utilizing the ARIMA method in forecasting PT Gudang Garam Tbk's future stock prices.